Parâmetros seminais e espermáticos, estocagem e criopreservação do sêmen do surubim do Iguaçu, Steindachneridion melanodermatum (Garavello, 2005) - Marcos, Ronan Maciel (2012)
The aim of this work were: evaluate sperm and seminal parameters of surubim-do-Iguaçu males and evaluate the effect of dilution, temperature and storage time of semen on them, besides determine the viability and describe the kinetics of activation of sperm cells of S. melanodermatum cryopreserved in different extenders. For the realization this work was divided into two sections: a) Spermatic and seminal parameters of surubim do Iguaçu, and short-term semen storage. It was collected semen from nine males hormonally induced. The spermatic parameters evaluated were: sperm motility (MOT), curvilinear velocity (VCL), straight-line velocity (VSL), average path velocity (VAP), sperm velocity (SV), time total of sperm activation (TEMP), sperm concentration (CONC), normal sperm morphology index (NORM), seminal plasma osmolality (OSM) and pH of semen (pH). Samples of semen were stored in microtubes to evaluate the effect of dilution (aqueous solution containing 5% fructose and 5% milk powder), temperature (10 and 25°C) and storage time (0, 5, 9, 18 , 27, 36, 45, 54 hours) on the MOT, VCL, VSL, VAP and TEMP. Males released on average 10.57 ± 6.28 mL and the sperm showed 99,86±0,31% of MOT, 185,58±14,11μm.s-1 of VCL, 49,15 ±4,66μm.s-1 of VSL, 87,02±4,13 μm.s-1 of VAP, 106,52 ±4,45μm.s-1 of VE, 79,31±5,62s of TEMP, 1,03x1010±3,65x109 células.mL-1 of CONC, 75,81±5,71% of NORM, 258,78±29,36mOsm of OSM and 7,11±0,31 of pH. b) Motility and kinetics activation of sperm cells cryopreserved in different extenders. Were collected semen samples from five males, hormonally induced, these submitted to the protocol of cryopreservation with the use of twelve extenders, formulated with the use of glucose, fructose, milk powder, DMSO, propylene glycol and methanol. The cryopreserved semen was thawed and evaluated for the parameters: sperm motility (in 10 seconds after activation), theoretical initial motility, sperm velocity, index of normality and the elapsed times for 75%, 50% and 25% of the sperm stay mobile. The fresh semen was evaluated for the same parameters. The solution containing 2.5% fructose, 5% milk powder and 10% methanol had higher (P <0.05) rate of normality (71.13 ± 4.79%) and higher initial motility (85.56 ± 15.31%). By using the solution containing 5% fructose, 5% milk powder and 10% methanol was found highest averages for the parameters: sperm motility in 10s after activation (78.99 ± 27.20%), sperm velocity (75.62 ± 18.76 μm.s-¹) and this solution prolonged the sperm activation. The semen samples stored undiluted and maintained at 10 or 25°C showed higher averages for MOT. Is indicated storage of semen S. melanodermatum un diluted until 27 hours and cryopreservation using the extender solution containing 5% fructose, 5% milk powder and 10% methanol in aqueous solution.